Incentives through Inventory Control in Supply Chains - Zhan Qu; Horst Raff; Nicolas Schmitt (Kiel Centre for Globalization (KCG), 2017)
The paper shows that taking inventory control out of the hands of competitive of exclusive retailers and assigning it to a manufacturer increases the value of a supply chain especially for goods whose demand is highly volatile. This is because doing so solves incentive distortions that arise when retailers have to allocate inventory across sales periods, and thus allows for better intertemporal price discrimination. Assigning inventory control to a manufacturer is also shown to have effects on total inventory and social welfare.
Keywords: L11; L12; L81; 330; inventory; supply chain; demand uncertainty; storable good; price discrimination